PERAN KOMUNITAS DALAM MENGELOLA HUTAN KOTA: KASUS SANGGA BUANA, JAKARTA SELATAN - Novianti, Kurnia; Rahadian, Angga Sisca (Jurnal Masyarakat dan Budaya, 2015)
Urban forest is one of few alternatives to balance the deterioration in the quality of environment. Jakarta has 14 urban forests under the coordination of the Department of Marine and Fisheries. In contrast, there is also urban forest located in South Jakarta and managed by local community to provide not only for preserving environment but also providing social life for local inhabitants. This paper aims to analyze the roles of community in the urban forest management. In addition as a city buffer, urban forest is also have an immense economic potential to improve the well-being of local community. The case of urban forest described in this paper is Sangga Buana located at Lebak Bulus, South Jakarta. Through observations, in-depth interviews, and focus group discussions, it is found that the responsibility in managing urban forest depends not solely on the government but also on the community. The Sangga Buana urban forest is one of examples where the local community practically has managed the forest. Since the very first time this urban forest was developed, the contribution of the government in the development of this site is almost unheard. This lack of support, however, initiates the local community to manage and develop the forest. The roles of local community in the urban forest management are arranged as a long-term participation. As such, the local community is transformed from merely a passive stakeholder of urban forest to active management of it. The forest now functions not only as a buffer to prevent floods and drought, but also provides economic benefits for the local community. In this sense, this urban forest has appeared as embodiment of the concept of sustainable green environment. Keywords: urban forest, Sangga Buana, role of community, green environment, Jakarta